环氧树脂混合物 (2018)
本发明的具体实施例公开烧结滑石粉。该烧结滑石粉包含：具有第强度的从约29°至约30°的第X-射线衍射尖峰，以及具有第二强度的从约25°至约27°的第二X-射线衍射尖峰，其中该第强度大于该第二强度。 Embodiments of the present disclosure set forth a sintered talc powder. The sintered talc powder comprising a first X-ray diffraction peak from about 29° to about 30° and having a first intensity and a second X-ray diffraction peak from about 25° to about 27° and having a second intensity, wherein the first intensity is greater than the second intensity.